(untitled) - FAO (Rome, 1997)
The information contained in this publication - the result of a workshop for young experts in rural development and agrarian reform - offers a unique golbal view of changes that have taken place in the developing world since the end of the cold war. Through the national and regional case studies that were presented at the workshop, as well as the reports from the workshop's round table discussions, it is possible to develop a greater a greater understanding of the reaction to those changes.
Keywords: rural development,training manuals